Sustainability and Innovation: leveraging the potential of agro-industrial waste whey and grape pomace in the rise of sports drinks (Agroindustrial Science, 2025)
By-products are generated in the agri-food industry and are often considered as waste; however, they are still rich in proteins, antioxidants and other beneficial compounds. This is an opportunity to revalue them in the development of ingredients for the food industry, reducing environmental impact and promoting a circular economy. Foods and beverages made from these ingredients contribute to sustainability and offer nutritional benefits that can improve sports performance and metabolic control. This review assesses the potential of these by-products as functional ingredients in sports nutrition, meeting the demands for beverages in this sector, the interest in health and an active lifestyle; highlighting the opportunity to generate innovative products that align with consumer expectations regarding environmental and health concerns.
Keywords: Agro-industrial by-products; beverages; athletes; whey; grape pomace